Covid-19 Vaccinated and Positive Rate of Infection in Israel and the United Arab Emirates - Alberto Boretti; Sarim Al Zubaidy (Dr. Sulaiman Al Habib Medical Journal)
Thanks to the high vaccination rates posted in Israel and the United Arab Emirates since mid-December 2020, by end of March 2021 a significant portion of the population has been vaccinated. This adds to the percentage of those who have been infected and have recovered, protected to a different extent depending on the time of infection. The manuscript tries to understand the effect of vaccinated and previously infected on the number of new cases, based on the available data for the number of cases, tests, vaccines' doses, and fatalities. The positive effect of vaccinations on the new cases has been masked so far by confounding factors, as it is not evidenced by the proposed data.